Sobre o estilo de Demétrio: um olhar crítico sobre a Literatura Grega (tradução e estudo introdutório do tratado) - Gustavo Araujo de Freitas (2011)
On Style is a work surrounded by many doubts; first of all, the question of dating and authorship. Among authors, dates range from III century BC and II AD, and nothing is known about Demetrius, who is assigned by the treatise to certain statements found in manuscripts. In any way, it can be assumed as more likely that this work was written in the first century BC, reflecting concepts of III and II centuries BC. The uncertainty in respect to its audience, plus a considerable number of critical reflections on literary works, led many authors to question whether the treatise would be a handbook of rhetoric or a work of literary criticism. The most reasonable answer to these questions is that it is a handbook, not for beginners, but for those who have already taken rhetorical courses of education and have learned to write the so-called progymnasmata. It does not rule out the literary criticism, on the contrary, it is not only present but also constitutes an important tool for rhetorical theory. However, despite all this discussion, little has been explored about this criticism, so that perceptions of Demetrius about authors cited by him remain, in most cases, still unexplored. Thus, the aim in the introductory study of this work is to try to unravel the paths that lead to this criticism, and thereby to better understand what Demetrius has to say about the texts of these authors. Following, this work will bring a translation of the work, still unpublished, for the Portuguese Language. The notes can elucidate this text, yet so enigmatic for most of the readers of this language.